2003
DOI: 10.1016/s0254-0584(03)00059-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform distribution of plastic strain in duplex steel during TEM in situ deformation

Abstract: Transmission electron microscopy (TEM) in situ straining experiments were carried out on duplex ferritic-austenitic steel. Localization of strain as a common feature during slip transfer from the austenite to the ferrite has been noticed. The character of strain localization depends on the orientation relationship between the phases. A possible influence of the TEM specimen geometry on the mechanism of plastic deformation of the ferritic-austenitic steel was considered by comparing the results with those of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Zielinski et al [19] studied the evolution of dislocation structure in a solution annealed DSS by in situ TEM straining experiment and reported that the evolution of dislocation structure during straining was dependent on the orientation relationship between the two phases. In the case of special orientation relationships, the slip markings in the ferrite, produced by the dislocations emitted from the boundary, indicate the compatibility of easy slip systems in the two phases, which favours a strong localization of strain.…”
Section: Tensile Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Zielinski et al [19] studied the evolution of dislocation structure in a solution annealed DSS by in situ TEM straining experiment and reported that the evolution of dislocation structure during straining was dependent on the orientation relationship between the two phases. In the case of special orientation relationships, the slip markings in the ferrite, produced by the dislocations emitted from the boundary, indicate the compatibility of easy slip systems in the two phases, which favours a strong localization of strain.…”
Section: Tensile Behaviourmentioning
confidence: 99%
“…However, this grade of steel embrittles when exposed in the temperature range of 280-500 • C limiting its application to temperatures below 280 • C. This phenomenon is termed 475 • C embrittlement as the rate of embrittlement is highest at 475 • C [13][14][15]. The embrittlement changes the tensile [16][17][18][19][20][21][22], fracture [23][24][25][26][27][28][29][30][31][32] and fatigue [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]23,48,49] behaviour of this steel.…”
Section: Introductionmentioning
confidence: 99%
“…Elongated J layers in the cold rolled specimen turns to a row of roughly equiaxed J grains separated from each other. Some authors 11 have reported that the phase boundaries play the key role in the plastic deformation. The elongated austenite grains show the signature of cold rolling operation, which was not recovered fully after isothermal treatment.…”
Section: Effect Of Heat Treatment On Microstructure Formationmentioning
confidence: 99%
“…The microstructure (strain heterogeneities) is of prime importance in damage and the initial crack [9]. The differences in behavior of each phase and the strain heterogeneities were studied by other authors using various techniques (SEM, TEM, EBSD, AFM) [10][11][12]. Strain heterogeneities between phases in duplex stainless steel were examined experimentally during in situ test using the EBSD technique and Digital Image Correlation (DIC) [13].…”
Section: Introductionmentioning
confidence: 99%